The behavior of bachelor degree students at Kasem Bundit University in using smartphones - Srisa, Sittichai (Journal of Humanities and Social Sciences Loei Rajabhat University, 2019)
The objective of this study is to examine the behavior of bachelor degree students at Kasem Bundit University in using smartphones. This research is quantitative research which uses questionnaires as the main tool for data collection. The samples of this research are 380 bachelor degree students in 2017. The statistical analysis tool for the research was the Frequency, Mean, and Standard Deviation. The findings indicate that 1. Personal information consists of gender, age, university year, faculty, native domicile and income, most of the samples are female. The average age is between 21 -22 years old. Most of the samples study at the Faculty of Business Administration. Most of them live in Bangkok Metropolitan Region, and also earn income from family supported. 2. The behavior in using the smartphone in overall shows at Often Level which can break down into 3 categories from the highest average score to the lowest average score as 1. The situation behavior 2.propose behavior 3.readiness behavior.